Assessment of Heavy Metals Concentration in Water and Fish of Dalmaj Marsh, Iraq - Al-Sulttani, Ahmed H.; Beg, Ayad Ali Faris; Dahash, Ali Hameed (Iraqi Journal of Science, 2022)
Most marshes in Iraq face several challenges as aquatic environments, including pollution by various chemical agents and heavy metals. The current study deal with an analysis of the water quality of Dalmaj marsh as one of the closed aquatic environments in the middle parts of Iraq located between latitudes 32ᵒ 05′ to 32ᵒ 23′N and longitudes 45ᵒ 10′ to 45ᵒ 38′ E. The marsh is suffering from a shortage in water supply, especially during the summer. It will lead to a concentration of heavy metals that are washed and transported to the marsh from the surrounding watersheds through surface runoff. This work aims to analyze water and fish samples to assess heavy metals and their accumulated risk in fish tissues based on many indices. The 16 samples of water and nine samples of fish are collected and analyzed for concentration of heavy metals, i.e., Lead (Pb), Chromium (Cr), Nickel (Ni), Cadmium (Cd), Copper (Cu), Zinc (Zn). The water analysis results indicate that Chromium (Cr) only comes below the permissible limit in water. At the same time, the composite heavy metals pollution index (HPI) identified that the water samples are varied from light pollution to malignant pollution. Regarding fish samples, three indices, i.e., BAF, EDI, and HI, are used to test the accumulated concentration of heavy metals in fish tissues and to point out their risk to consumers. The results indicate that Pb and Ni are the more hazardous metals accumulated in many fish samples with increasing fish weight, while hazard index (HI) is an additive index of all tested heavy metals, indicating concern risk from most fish samples. The study recommends testing the marsh water pollution periodically.